Nanoscale interfibrillar adhesion in UHMWPE fibers. Issue 5 (19th December 2017) - McDaniel, Preston B.; Strawhecker, Kenneth E.; Deitzel, Joseph M.; Gillespie, John W.
ABSTRACT: The goal of this research is to quantify the fibrillar adhesive energy in ultra‐high molecular weight polyethylene fibers, characteristic of nanoscale fibril interactions. Quantification of these energies is vital to the understanding of fibrillar deformation mechanisms that have been shown to play an important role in fiber performance. This is achieved through the development and implementation of a nanosplitting technique developed through the use of AFM‐enabled nanoindentation. This technique allows the quantification of nanoscale adhesive energies through careful monitoring of load and unload curves as well as examination of the residual split through high‐resolution AFM images. Results indicate that the average nanoscale fibril adhesive energy is over 3 times larger than the energy expected from van der Waals interactions alone. This indicates that a significant degree of physical interactions exist between fibrils, beyond van der Waals interactions, in the form of tie‐molecules, fibrillar network junctions, and bridging lamellar crystals. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 391–401 Abstract : Ultra high molecular weight polyethylene (UHMWPE) fibers are commonly used in high performance applications due to their high specific strength and stiffness derived from the extended chain polymer chains. An AFM nanoindentation based methodology has been developed to quantify the adhesive energy between fibrils in UHMWPE fibers.